2023
DOI: 10.1007/s10648-023-09736-2
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Association Between the Big Five Personality Traits and Student Achievement: Meta-Analytic Evidence on the Role of Domain Specificity and Achievement Measures

Abstract: Students’ academic achievement is a central predictor of a long list of important educational outcomes, such as access to higher education and socioeconomic success. Prior studies have extensively focused on identifying variables that are related to academic achievement and an important variable in this context appears to be students’ personality. Notably, although findings from more recent studies suggested that the association between student achievement and personality varies by the subject domain (language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 116 publications
0
5
0
Order By: Relevance
“…Tackman et al (2019) also referred to the roles and functions of the family in fostering children's conscientiousness (Tackman et al, 2017). Furthermore, as Meyer et al (2023) pointed out, conscientiousness as a personality trait leads to behaviors such as active engagement in academic tasks and duties (Meyer et al, 2023). This sets the stage for conscientiousness to further strengthen the relationship between a positive emotional, emotional, and supportive family atmosphere and academic performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tackman et al (2019) also referred to the roles and functions of the family in fostering children's conscientiousness (Tackman et al, 2017). Furthermore, as Meyer et al (2023) pointed out, conscientiousness as a personality trait leads to behaviors such as active engagement in academic tasks and duties (Meyer et al, 2023). This sets the stage for conscientiousness to further strengthen the relationship between a positive emotional, emotional, and supportive family atmosphere and academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The moderating ability of conscientiousness in the relationship between perceived family atmosphere and academic performance lies in the role that conscientiousness plays according to the approach of the pervasive effect of personality traits on behaviors and decisions in different conditions (Ching, 2021). In fact, since conscientiousness facilitates behaviors such as active engagement in academic tasks and duties (Meyer et al, 2023), it has the ability to also affect the influence of family atmosphere on performance. Supporting this, Wang et al (2023) in their study showed that a variable like conscientiousness, by creating a sense of efficacy and individual identity, lays the groundwork for enhancing academic progress (Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has linked both personality traits and SEB skills with academic performance. For example, meta-analyses of the Big Five traits and school grades have identified Conscientiousness as the most robust predictor of higher grades, with effects that generalize across education levels and geographic regions (Mammadov, 2022;Meyer et al, 2023;Poropat, 2009). As for SEB skills, meta-analyses have found that students exposed to social and emotional learning interventions tend to earn higher school grades, both immediately following the intervention and in subsequent years (Durlak et al, 2011;Taylor et al, 2017).…”
Section: Relations Of Personality Traits and Seb Skills With Academic...mentioning
confidence: 99%
“…This conceptualization, and the present findings, suggest that SEB skills and traits may best predict different kinds of outcomes. Specifically, skills may best predict outcomes reflecting someone's thoughts, feelings, or behavior in specific, high-stakes situations, whereas traits may best predict outcomes that reflect the gradual accumulation of someone's behavior over time and across situations (Marcus et al, 2007;Meyer et al, 2023;Ployhart et al, 2001).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Among the measurement for assessing non-cognitive skills in individuals are personality traits and commonly categorized to the big five personality traits. These five indicators including extraversion, agreeableness, conscientiousness, openness to experience, and neuroticism, collectively offering valuable insights into an individual's character and disposition (Luo et al, 2023;Akbari et al, 2023;Meyer, et al, 2023;Vize et al, 2023).…”
Section: Introductionmentioning
confidence: 99%